A highly sensitive and selective method for analysis of biomarkers of diisocyanate exposure in human urine by high-performance liquid chromatography with intramolecular excimer-forming fluorescence derivatization. Issue 17 (8th November 2018) - Sun, Zhiwei; Jin, Qianqian; Yu, Yanxin; Cheng, Jie; Ji, Zhongyin; Li, Guoliang; You, Jinmao
Abstract: Urinary aromatic diamines are exposure biomarkers of diisocyanate which are highly irritating to skin, mucosa and the upper respiratory system. In this study, a highly sensitive and selective high-performance liquid chromatography-fluorescence detection (HPLC-FLD) method was developed for determination of three aromatic diamines, 4, 4′-methylenedianiline (MDA), 2, 4-toluenediamine (4TDA) and 2, 6-toluenediamine (6TDA) exposed to corresponding diisocyantes in human urine. The whole idea is based on an intramolecular excimer-forming fluorescence derivatization using 4-(1-pyrene)butanoyl chloride (PBC), followed by performing HPLC-FLD analysis.The resulting polypyrene-labeled derivatives of these aromatic diamines provided intramolecular excimer fluorescence at the emission wavelength of 475 nm wavelengths, which was shifted markedly to the higher emission wavelengths as compared with the wavelengths of the pyrene monomer. Under this condition, interferences such as amino acids and biogenic monoamines gave no peaks. It was found that using PBC derivatization, it was possible to improve the sensitivity and selectivity toward aromatic diamines. The limits of detection (LODs) were in the range of 0.30–0.52 ng/L, while the limits of quantitation (LOQs) between 1.05 and 1.63 ng/L. The intraday and interday precision was in the range of 3.6–4.5% and 4.1–5.7%, respectively. The proposed method was successfully applied to the quantitation of these exposure biomarkers in human urine samples. Graphical Abstract: